Flying the Atlantic - and selling sausages have a lot of things in common - Earhart, Amelia, 1897-1937
Amelia Earhart discusses the motivations for her transatlantic solo flight. Periodical covers have been included with many of the digitized articles whether they relate to them or not. Extra pages not part of the article in question may also be present.